IMPLEMENTASI PERMENKES NOMOR 1464/MENKES/PER/X/2010 TENTANG IZIN DAN PENYELENGGARAAN BIDAN DALAM MENDUKUNG KESEJAHTERAAN IBU ( Studi di Kabupaten Cilacap ) - Suswati Suswati (Jurnal Idea Hukum, 2016)
Everyone has the right to live physical and spiritual prosperity (UUD 1945, Article 28 H paragraph (1)). Everyone has the right to health (Health Act 2009 Section 4); Maternal health efforts should be aimed at maintaining the health of mothers and reduce maternal mortality, maternal health services regulated by Permenkes No. 1464/Menkes /Per/X/2010 (the Health Act of 2009 Section 126). This research is qualitative sociological juridical approach (Socio Legal Approach), retrieval of data through observation and interviews, the twenty midwives, and twenty patients, as well as a five-person team informant who is a manager and supervisor of midwives practice.The results showed that: The implementation of Permenkes No. 1464/Menkes/Per/X/2010 on Permit and Implementation of midwife is able to support in the welfare of the mother, by virtue of the licensing requirements fulfilled 90%, organizing practice standards compliance services 78%, guidance and supervision is done by the health center level, and the rights of mothers in Public Health Center include: Respect the rights of the mother; Giving the mother's health information; Requesting approval of the action; Keep a secret; and service standards are fulfilled, to get health care safety and quality, the mother is able to give birth to a qualityÂ  and healthy generation, and to avoid the complications which allows the maternal mortality as an indicator of welfare of the mother.Keywords: Permenkes number 1464 of 2010, Welfare mothers.Â Â